Developing ESP learning materials for airport ground handling services students: A needs analysis - Olivia Azhar, Herida Panji; Masyi’ah, Anita Nur (Universitas Ahmad Dahlan, 2023)
English for Specific Purposes (ESP) plays a pivotal role in enhancing the communicative competence of students preparing for careers. In order to develop the ESP learning materials for ground handling students, this study focuses on the needs analysis. The needs analysis will capture two aspects: 1) The participants’ perspectives on the development of ESP learning materials 2) the use of the English language by the airport ground handling crews. A mixed-method design was employed, incorporating surveys and interviews. The 397 participants involved students, instructors, and airport ground crews. Descriptive statistics were used to unveil the trends in the findings, and simultaneously, data reduction, data display, and drawing verification were used to delve into the participants perspectives. The validity and reliability of the survey questionnaire were tested, and member checking was used to justify the credibility of the qualitative findings. The findings provide valuable input for the development of ESP learning materials that are contextually relevant and aligned with the needs of airport ground handling services students.